MULTI-SENSOR FIBER-OPTIC CONVERTER OF BINARY MECHANICAL SIGNALS - V.M. Grechishnikov; A.E. Kapiturov; K.B. Nersisyan; O.V. Teryaeva (Надежность и качество сложных систем, 2022)
Background. The design and principle of operation of a multi-sensor fiber-optic converter of binary mechanical signals based on a fiber-optic digital-to-analog converter (DAC) of a serial type is considered. Materials and methods. The method of linearization of the device transformation function, its mathematical and simulation models are described. Results and conclusions. The advantages of the proposed device in comparison with an analog based on a parallel DAC are substantiated.